Generation Z’s Perception of Political Memes in the Context of Digital Media Literacy Education - Fitra Hadi Khaz; Gessya Aprilia Syahrika Putri; Nabilla Maharani; Salsabila Rahmayanti; Riski Hariadi Utomo (Civiliza Publishing, Indonesia., 2025)
Rapid technological developments have made human life much more practical and easier. One such technology is social media. Political memes are increasingly dominant on social media and have become a tool for the rapid and easily accepted dissemination of political messages. The purpose of this study is to examine how Generation Z views political memes as a propaganda instrument in the 2024 General Election. This study used a literature review method with both a literature review and content analysis. Data analysis was conducted descriptively and interpretively by integrating Robert M. Entman's framing theory and Chong and Druckman's framing theory. The findings indicate that Gen Z views political memes as an engaging and creative communication medium but are also aware of the risks of information manipulation within them. Political memes are considered effective in increasing political attention and engagement, but their impact depends on an individual's level of digital literacy.